Cambridge learner's dictionary - Cambridge University Press (Cambridge, Cambridge University Press, 2009)
Summary: Third Edition Of The Cambridge Learner'S Dictionary Is A 'Must Have' For Any Intermediate Level Student Looking To Develop Their Language Skills. With New Features, Including Word Partner And Thesaurus Boxes, It Offers Even More Support For Students Whether They Are Learning English For Work, Pleasure Or Preparing For An Exam, Particularly Pet Or Fce.
Donated by: Student
Keywords: english language -- dictionaries -- textbooks for foreign speakers